San Francisco banner - Sahl, Ted (photographer):::Creator::::::::::::
Marchers carry a long sign that reads, "San Francisco" during the National March on Washington for Lesbian and Gay Rights. On the left a man holds a sign where "Stonewall, Fight Back!" is legible.